Fungos Endofíticos Dark Septate em arroz silvestre Oryza glumaepatula Steud - Ribeiro, Karen Gonçalves (2011)
The endofophytic fungi such as “dark septate” or DSEF can be promoters of plant growth. However, there are few studies com this group of fungi. The objective of this study was to characterize DSEF fungi obtained fron plants collected in enviroments Oryza glumaepatula Amazon. The plant roots of twelve O. glumaepatula samples were sectioned, disinfected, and placed in plates with agar-malte medium added of chloramphenicol and trimethoprim sulmametazol more. The isolates were evaluated in relation of dark septate characteristics and stored in distilled water, and in distilled water added of glycerol. All fungal isolates considered DSEF were reinoculated in plants of O. glumaepatula, and inoculated in 5 in Oryza sativa and also genetically characterized by amplifying and sequencing the region ITS1-5.8S-ITS2. The agar-malte medium was efficient to isolate DSEF, resulting in more than 46 isolates. The distilled water and also distilled water added of glycerol were efficient to maintain the fungus culture at least 12 months. All 46 fungal isolates were reinoculated to colonize roots O. glumaepatula and 5 of these isolates were able to colonize O. sativa, not trigger symptoms of pathogenicity. Genetics analysis of isolates showed that these fungi have low similarity between them and have no similarity to fungi DSEF already described and present in the database of Genbank, indicating that the methodology allowed the acquisition of several fungal species and the species O. glumaepatula houses high diversity of this group of fungi.